PAYUNG HUKUM ZAKAT DI ERA OTONOMI DAERAH : MENIMBANG RELEVANSI PERDA ZAKAT PASCA UU NO. 23 TAHUN 2011 - MUHTADA, DANI (UIN Sunan Kudus, 2016)
The era of regional autonomy has increased the number of regulations in Indonesia, including the regulation of zakat. This article peeling relevance zakat regulations in the era of regional autonomy after the enactment of Law No. 23 of 2011 on the Management of Zakat. This article began by discussing various zakat regulations that emerged in Indonesia in the era of regional autonomy, followed by a discussion of the two national regulations on zakat: Law No. 38 of 1999 and Law No. 23 of the year 2011. After that article analyzing the material contained within these two laws Zakat and compared with a charge contained in bylaws zakat alms to evaluate the relevance of regulation after the enactment of Law No. 23, 2011. This article underlines that post Zakat Law, enacted in 2011, local regulations zakat old and new is no longer relevant. Although the issuance of new regulations charity possible, this article suggested that the local government and management to optimize the empowerment of zakat through national legal instruments that already exist.